A new species of Magnimyiolia Shiraki (Diptera: Tephritidae: Trypetinae) and new records of Acanthonevrini from India - Singh, Shakti Kumar; David, K. J.; Kumar, Dinesh; Ramamurthy, V. V. (Zootaxa, 2015)
A new species of the subfamily Trypetinae, Magnimyiolia perennifascia Singh & David, sp. nov. (Trypetini) is described from India. Two species of subfamily Phytalmiinae, Ectopomyia baculigera Hardy and Ptilona conformis Zia (Acanthonevrini) are recorded for the first time from India. An updated key to Oriental species of Magnimyiolia Shiraki is provided.